Components Analysis of Bioactive Essential Oil Combinations (Lavender, Lemon, and Cinnamon) by Gas Chromatography-Mass Spectrometry and their Activities against In Vitro Photoaging on Hairless Rat Dorsal Skin - Hardi Astuti Witasari; Kintoko Kintoko; Warsi Warsi; Salsabila Ramadhan; Nadiya Utari; Tsania Taskia Nabila (Faculty of Pharmacy, Universitas Gadjah Mada, 2022)
The essential oil of lavender, lemon, and cinnamon (LaLC) combination is rich in antioxidants and potentially be used as an anti-wrinkle and strengthens the collagen tissue. Ultraviolet B (UVB) radiation is a free radical source that accelerates the aging process and reduces collagen production. This study aims to characterize the chemical components of each oil and determine the best combination as an anti-wrinkle substance. The test was conducted on twenty-four Wistar male rats (Mus musculus) that were divided into six experimental groups consisting of the normal (N), control (C), vehicle control (V), first treatment (T1), second treatment (T2), and third treatment (T3) groups. Each sample was rubbed upon, and the UVB irradiation was administered frequently to each subject. The embedded skin specimen was analyzed using a digital-capable microscope. Data were analyzed through the Kolmogorov-Smirnov normality test, one-way analysis of variance (ANOVA), and the post-hoc Tukey's Honest Significant Difference test. Lavender, lemon, and cinnamon essential oils contained each most significant component, which was linalool (41.46% peak area), dl limonene (44.74% peak area), and 2-propenal, 3-phenyl- (CAS) (53.89% peak area), respectively according to the Gas Chromatography-Mass Spectrometry (GC-MS) analysis. The T1 showed the best score of all parameters and did not show significant significance compared to the N group. In conclusion, the 1:1:3 combination of LaLC is better in preventing in vitro photoaging than other treatment groups.